Techno economic and environmental assessment of wind assisted marine propulsion systems. (15th July 2016) - Talluri, L.; Nalianda, D.K.; Kyprianidis, K.G.; Nikolaidis, T.; Pilidis, P.
Abstract: In recent years, the increase in marine fuel prices coupled with stricter regulations on pollutant emissions set by the International Maritime Organization have promoted the research in new propulsion technologies and the utilisation of cleaner fuels. This paper describes a novel methodology to enable quantifying and evaluating the environmental and economic benefits that new technologies and fuels could allow in the marine sector. The proposed techno economic and environmental analysis approach enables consistent assessment of different traditional propulsion systems (diesel engine and gas turbine) when operated in conjunction with a novel environmental friendly technology, such as a vertical axis wind turbine. The techno-economic and environmental assessment is focused on the potential reduction in fuel consumption and pollutant emissions that may be accrued while operating on typical Sea Lines Of Communication (Mediterranean, North Sea, Atlantic). The study demonstrates the benefits of the installation of two vertical axis wind turbines on the deck of a ship in conjunction with conventional power plants. The analysis indicates that the performance of the wind turbines and the corresponding benefits strongly depend on the routes and environment in which they operate (therefore favourable wind conditions) allowing fuel savings from 14% (in the gas turbine case) to 16% (in the diesel engine case). The study also indicates that possible benefits may diminish for weak wind conditions. The results reported in this paper establish the economic benefits of installing vertical axis wind turbines in conjunction with conventional technology (Diesel and Gas Turbine Power plants) when installed on a ship travelling through the Atlantic Ocean. The primary purpose of this study is to introduce a methodology to demonstrate the application, performance and economic benefits of the technology at a preliminary design phase and further form a foundation for more elaborate analysis on the subject in the future. Highlights: Novel methodology applied for evaluation of marine propulsion technologies. Potential of VAWT as an assisting technology for conventional marine propulsion. Environmental gain utilising gas turbine using NG over diesel engine burning MDO.